Candidate testis-determining gene, Maestro (Mro), encodes a novel HEAT repeat protein. - Smith, L; Van Hateren, N; Willan, J; Romero, R; Blanco, G; Siggers, P; Walsh, J; Banerjee, R; Denny, P; Ponting, C; Greenfield, A (2003)
Mammalian sex determination depends on the presence or absence of SRY transcripts in the embryonic gonad. Expression of SRY initiates a pathway of gene expression resulting in testis development. Here, we describe a novel gene potentially functioning in this pathway using a cDNA microarray screen for genes exhibiting sexually dimorphic expression during murine gonad development. Maestro (Mro) transcripts are first detected in the developing male gonad before overt testis differentiation. By 12.5 days postcoitus (dpc), Mro transcription is restricted to the developing testis cords and its expression is not germ cell-dependent. No expression is observed in female gonads between 10.5 and 14.5 dpc. Maestro encodes a protein containing HEAT-like repeats that localizes to the nucleolus in cell transfection assays. Maestro maps to a region of mouse chromosome 18 containing a genetic modifier of XX sex reversal. We discuss the possible function of Maestro in light of these data.